PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA PEMBELAJARAN GEOGRAFI TERHADAP HASIL BELAJAR - Suminarsih, Eka; Tampubolon, Budiman; Anasi, Putri Tipa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to analyze how much influence the application of the use of the model of project learning aed learning on learning geography on the learning outcomes of class X students of SMA Negeri 2 Sungai Raya. The research method used was an experimental method, while the form of research used was a quasi-experimental design with the type of non-queuing control group design. The population in this study were all students of class X IPS SMA Negeri 2 Sungai Raya, namely tendiri from class X IPS 2 and IPS 3. Research samples, namely 30 control class students and 34 experimental class students as many as 64 students. Data collection techniques used in this study were measurement techniques, the instrument used was in the form of a multiple choice test with a total of 50 questions. The results of the data analysis, obtained an average student learning outcomes in the control class 58.16 and the experimental class of 70.08, the results of hypothesis testing (t-test) using t-test obtained t 3.5438 and 1.6706 (significant level ( a) -5% and dk -38) show that tng is greater than tahd then Ha is accepted. This means that there are differences in learning outcomes between students who are taught by applying the project based learning model. From the calculation of the effect size, 0. 0,972   (high category) is obtained. This means that the project based learning model has a moderate effect on the learning outcomes of students of class X IPS IPS SMA Negeri 2 Sungai Raya. Keywords: Project Based Learning Model, Learning Outcomes, Geography